Cigarette Taxes and Youth Smoking: Updated Estimates Using YRBS Data - Benjamin Hansen; Joseph J. Sabia; Daniel I. Rees (Institute for the Study of Labor (IZA), 2015)
Using data from the state and national Youth Risk Behavior Surveys for the period 1991-2005, Carpenter and Cook (2008) found a strong, negative relationship between cigarette taxes and youth smoking. We revisit this relationship using four additional waves of YRBS data (2007, 2009, 2011, and 2013). Our results suggest that youths have become much less responsive to cigarette taxes since 2005. In fact, we find little evidence of a negative relationship between cigarette taxes and youth smoking when we restrict our attention to the period 2007-2013.
Keywords: I18; H71; 330; cigarette tax; tobacco control; youth smoking